2020
DOI: 10.1016/j.ihj.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transcatheter closure of patent ductus arteriosus with the off-label use of large occluders (≥16 mm)

Abstract: Objective Transcatheter closure is the first-choice strategy for the management of appropriate patients with patent ductus arteriosus (PDA). The management of large PDAs is challenging due to the limited available sizes of approved devices and the inherent risks of surgical ligation, especially in adults with calcified PDAs. This study aimed to assess the outcomes of the off-label use of large occluders at a tertiary center. Methods This retrospective review included pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The majority of operators choose to insert devices that are at least 2 mm larger than the narrowest point of the duct [ 10 ]. Kanabar et al (2020) suggested that in children, the size of the pulmonary end of the device should be at least 2 mm greater than the narrowest diameter of the PDA [ 11 ]. In adolescents and adults with severe pulmonary arterial hypertension, it should be twice the narrowest diameter [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of operators choose to insert devices that are at least 2 mm larger than the narrowest point of the duct [ 10 ]. Kanabar et al (2020) suggested that in children, the size of the pulmonary end of the device should be at least 2 mm greater than the narrowest diameter of the PDA [ 11 ]. In adolescents and adults with severe pulmonary arterial hypertension, it should be twice the narrowest diameter [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Amplatzer VSD muscular occluder, used off-label in this case, is approved for congenital VSD closure and has a diameter from 4 to 18 mm but has a long history of being used off-label to close large PDAs due to its larger maximum diameter. 11,12 A retrospective analysis of 447 patients with PDA and normal LVEF showed that 22.7% of patients had LV dysfunction after closure. The larger the PDA, the higher the risk of LV dysfunction, with 91% of patients having LV dysfunction when PDA sizes are >9 mm, but only 2.8% of patients with PDA of <3 mm had LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The Amplatzer VSD muscular occluder, used off-label in this case, is approved for congenital VSD closure and has a diameter from 4 to 18 mm but has a long history of being used off-label to close large PDAs due to its larger maximum diameter. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…A study on the comparison of outcomes for transcatether PDA closure in children and adults showed a decrease in EF values in both (13) .…”
Section: Discussionmentioning
confidence: 99%